Gender differences in electromyographic activation of some lower extremity muscles in subject with and without genu varum abnormality. - reza rajabi; malihe hadadnezhad; homan minoonejad; mahmood pour aazam (Vesnu Publications, 2014)
Introduction: mal-alignment of lower extremity especially at the knee can lead to injury due to impact on muscle activity and proprioception. Therefore the aim of present study was the gender differences of some lower extremity muscle activation in subject with and without Genu Varum. Material and Methods: subjects of present study was twenty four physically active students (group 1: six female with genu varum, group 2: six male with genu varum, group 3: six female without genu varum, group 4: six male without genu varum) of university of Tehran with the age ranged 18-22 years. For data collection, electromyography of gluteus medius, vastus medialis, rectus femoris and tensor fascia lata was performed and muscle activation was calculated. Result: Significant between groups differences reported in activity of Gluteus Medius (P=0.001), Rectus Femus (P=0.002) and Vastus Medialis (P=0.001) but no significant differences noted in activity of Tensor Fascia Lata (P=0.756).  The Bonferroni Post Hoc test results showed the significant differences in activity of Gluteus Medius (P=0.001), Rectus Femuri (P=0.003) and Vastus Medialis (P=0.003) of females and males with Genu Varum, also in activity of Vastus Medialis between females with and without Genu Varum Deformity (P=0.001). Discussion and Conclusion: Based on this study results, it's concluded that the subject with Genu Varum deformity suffering from neuromuscular control deficit and this deficits in females with Genu Varum was more than males, thereby this persons are more prone to injury than males. Key words: Genu varum deformity, electromyography activation, gender differences, vastus medialis, gluteus medius